ANALYSIS OF INDONESIAN EFL LEARNERS’ PERFORMANCE IN PRONOUNCING ENGLISH CONSONANT CLUSTER - Khodijah Jamilumulkillah; Fauzi Miftakh; Putri Kamalia Hakim (PROJECT (Professional Journal of English Education), 2023)
Pronunciation is essential in oral communication in order to convey messages effectively. Nevertheless, pronunciation can be challenging to master for EFL learners. One of the reason is because the different phonetic system between the native language and English as the target language. Particularly for Indonesian EFL learners, some research found that one of the difficulties that the learners encountered in learning English pronunciation is learners are unfamiliar with some sounds in English, since it does not exist in Bahasa Indonesia. Among them are consonant cluster, consonant cluster is scarcely found in Bahasa Indonesia. For example the word ‘thirst’ consist of three consonants, while Indonesian EFL learners are unfamiliar with this form.  This study aims to analyze the performance of EFL learners in pronouncing English consonant cluster. The study only analyze the production of 5 English consonant cluster, they are [θ], [ʃ], [gh], [ld], and [st]. The subject of this study is 5 students in vocational high school. The students was given a text that they have to read and record. Then the researcher analyze the students’ pronunciation of the consonant clusters. The research show that there are some errors that the students made while pronouncing the consonant clusters.   Keywords:  Pronunciation; Consonant Cluster; Error